The existence of Indonesian language: Pidgin or Creole - Dellis Pratika (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2016)
Indonesian language or sometimes called Bahasa is the national language of Indonesia. It was derived from Malay language and established as a national language in 1928. Until now, the Indonesian language keeps borrowing words from other languages. It was questioned whether the language was actually a pidgin that authorized into a creole since it was not only contained of Malay language but also languages that it was made contact with since colonialism eras, such as Dutch, English, Arabic, and other languages. This research used library study to find the data since it was not possible to trace the data in the field. This study was aimed to determine whether the Indonesian language was categorized into pidgin or creole. The result of the study revealed that Indonesian was not either pidgin or creole since the characteristics features did not meet any of them. It is believed that the Indonesian language was one of the means to achieve independence, but it is opened to receive lexicons from other foreign languages as the words keep increasing each year that can be seen in Kamus Besar Bahasa Indonesia (KBBI).